Psikologi Resiliensi Siswa dalam Pembelajaran Pendidikan Agama Kristen: Perspektif Alkitabiah dalam Menghadapi Tantangan Akademik dan Kehidupan - Siska Si'ki; Veronika Resta; Desmiati Pea; Jheane La'bi; Desrima Natalia Belopadang (Jurnal Pendidikan Dirgantara, 2025)
Modern students face high academic, social, and personal pressures, but Christian Religious Education has not yet maximized the potential of religious-based resilience. This study aims to: (1) analyze how the biblical values of faith, hope, and love can strengthen the components of students' psychological resilience in the cognitive, emotional, and spiritual dimensions; and (2) identify the integration mechanism between biblical teachings and psychological strategies in Christian Religious Education learning that can increase students' resilience in facing academic and personal stress. The method used is descriptive qualitative with a literature study approach to various journals, articles, and related academic sources. The results of the study show that the biblical values of faith, hope, and love are fundamental pillars that strengthen students' psychological resilience as a whole. Faith provides a foundation of self-confidence and personal competence, hope activates optimism and sustained motivation, while love builds healthy social relationships and essential emotional support. These three values work synergistically to strengthen students' emotional regulation, problem analysis, empathy, and self-efficacy. The deep integration of biblical teachings and psychology in PAK learning through biblical narratives, secure parenting relationships, supportive communities, and reflective feedback has proven effective in holistically improving student resilience. In conclusion, PAK learning that explicitly integrates biblical values with psychological resilience strategies is a transformative instrument for shaping students into individuals who not only perform well academically but are also spiritually strong, psychologically resilient, and ready to face complex life situations in accordance with the principles of 1 Corinthians 13:13 regarding faith, hope, and love